2003
DOI: 10.1097/01.iop.0000062848.26273.e5
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Assisted Orbital Volume Measurement in the Surgical Correction of Late Enophthalmos Caused by Blowout Fractures

Abstract: The measurement of orbital volume in patients with BOF can be used to predict the degree of late enophthalmos. Use of the orbital volume increment to determine the amount of implant material can improve the therapeutic outcome in the correction of late enophthalmos caused by BOF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
88
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(91 citation statements)
references
References 18 publications
1
88
0
1
Order By: Relevance
“…Since 1985 different orbital volume measuring techniques have been described using three-dimensional (3D) computed tomography (CT) imaging (Bentley et al, 2002;Bite et al, 1985;Carr et al, 1992;Cooper, 1985;Fan et al, 2003;Furuta, 2001;Koppel et al, 2003;Manson et al, 1986;Schuknecht et al, 1996). A number of studies have shown a strong correlation of these measurements with skull measurements (Acer et al, 2009;Cooper, 1985;Deveci et al, 2000).…”
Section: Discussionmentioning
confidence: 96%
“…Since 1985 different orbital volume measuring techniques have been described using three-dimensional (3D) computed tomography (CT) imaging (Bentley et al, 2002;Bite et al, 1985;Carr et al, 1992;Cooper, 1985;Fan et al, 2003;Furuta, 2001;Koppel et al, 2003;Manson et al, 1986;Schuknecht et al, 1996). A number of studies have shown a strong correlation of these measurements with skull measurements (Acer et al, 2009;Cooper, 1985;Deveci et al, 2000).…”
Section: Discussionmentioning
confidence: 96%
“…Prior studies ranged from 10 to 30 patients, thus having only 10 to 30 data points. [13][14][15][16][17][18] Our study included 15 cadavers with 525 total data points, which significantly increased the statistical power of our data over previous studies. The orbit is a closed space filled with noncompressible fluid.…”
mentioning
confidence: 92%
“…In about 8.5% of patients treated with orbital injuries a volume excess which leads to enophthalmos is noted, especially when the deep orbital cone is affected 8,30 . To prevent such complications, immediate repair of orbital injuries with the restoration of preinjury anatomy is indicated in extensive orbital floor and medial wall fractures 15 .…”
mentioning
confidence: 99%